RESEARCH ON THE EFFECTS OF DELAYS IN THE FORMATION OF FREIGHT TRAINS ON THE RAILWAY NETWORK OF UKRAINE - Kyman , A. M.; Prokhorchenko , A. V.; Liapin , D. Yu.; Tytarenko , O. Ye. (Systems and Technologies, 2026)
The article presents the results of a study of time-lag relationships between the volumes of wagons accepted for transportation and train-hours of delays of freight trains on the railway network of Ukraine. The aim of the study is to identify and quantitatively assess the temporal inertia of delay formation in the railway transportation process in order to substantiate the possibility of forecasting the development of network congestion and timely identification of bottlenecks in the railway network. The research is based on operational data of JSC Ukrzaliznytsia on wagon loading volumes and the duration of idle time of abandoned trains on the network. To analyse temporal relationships, cross-correlation analysis was applied using the Pearson linear correlation coefficient and the Spearman rank correlation coefficient. This made it possible to evaluate both linear and monotonic relationships between the studied indicators. Calculations were performed for lags in the range of up to 34 days, which allowed the identification of both short-term and medium-term inertial effects in the functioning of the railway system. The results of the analysis revealed a statistically significant time-delayed relationship between changes in the volumes of wagons accepted for transportation and train-hours of delays. It was shown that the strength of the correlation gradually increases with the growth of the lag and reaches its maximum values in the medium-term interval of 15-23 days, where the Pearson correlation coefficient reaches up to 0.66. The obtained results indicate the presence of pronounced temporal inertia in the functioning of the railway transportation process, when the consequences of increased traffic volumes manifest themselves with a significant time delay. In addition, spatial heterogeneity of lag effects was identified at the level of individual railway stations, where peak lags vary from 1 to 29 days depending on the role of a station in the network and its technological capacity. The obtained results demonstrate the potential of lag analysis for identifying critical periods of network congestion formation and for substantiating decisions on the introduction of temporary restrictions (conventions) on freight dispatching. A rule is proposed for determining the optimal time interval for introducing such conventional restrictions on the acceptance of freight for transportation. The practical significance of the study lies in forming an analytical basis for the development of decision-support systems aimed at enabling proactive management decisions for the early identification of critical bottlenecks within the railway network